Augmented Reality Flashcards for Arabic Vocabulary Learning - Ramadhani, Ummu Hanifah; Arifin , Moch. Bahak Udin By (Indonesian Journal of Islamic Studies, 2024)
General Background: Augmented Reality (AR) has emerged as a transformative technology in educational media, particularly for language learning. Specific Background: In the context of Arabic language acquisition, traditional methods often lack engaging, interactive elements that enhance vocabulary retention. Knowledge Gap: Existing literature has not sufficiently explored the integration of AR technology in vocabulary learning, particularly for specific themes like time. Aims: This study aims to develop AR Flashcards to facilitate mastery of vocabulary related to time in Arabic language learning at MA/SMA Muhammadiyah, utilizing the ADDIE model for product development. Results: The resulting Flashcards consist of thirteen interactive cards that present vocabulary in a sequence, enriching the learning experience through visual and gamified elements. Students can scan QR codes with minimal smartphone specifications, enhancing accessibility. Novelty: This research introduces a novel educational tool that combines AR technology with structured learning, providing a memorable and effective approach to vocabulary acquisition. Implications: The findings suggest that AR Flashcards can significantly improve students' understanding and retention of Arabic vocabulary, highlighting the potential for technology-enhanced learning environments in language education. Highlights: Interactive Learning: AR Flashcards provide an engaging way to learn Arabic vocabulary through visual elements. Structured Development: The product follows the ADDIE model, ensuring a systematic approach to educational tool creation. Accessibility: Students can use smartphones with minimal specifications to access the learning material via QR codes. Keywords: Augmented Reality, Flashcards, Arabic language, vocabulary mastery, educational technology.